Struktur dan Makna Verba Majemuk Bahasa Jepang V1+Komu - Onin Najmudin; Puspa Mirani Kadir; Novita Puspahaty (Makna: Jurnal Kajian Komunikasi, Bahasa, dan Budaya, 2020)
The verb komu is one of components of the VV lexical compound verbs. This research aims to identify structures and meanings of the lexical V1+komu compound verbs through to the Transivity Harmony Principle (THP) theory. The Transitivity Harmony Principle (THP) was used to examined the combination between V1 and komu as V2 based on argument structures of the verbs. The data gathered from Japanese language novel Ningen no Daichi that contained V1+komu compound verbs. The results showed that komu as a V2 can be combined with any various types of verb in V1, respectively; transitive+komu (e.g oshi-komu ‘push in’), unaccusative +komu (shizumi-komu ‘sink in’), and unergative+ komu (e.g abare-komu ‘go in violently’). Even combined with different types of verb in V1, komu was retained its argument structure; adding a goal phrase to verb in V1. The combinations of komu with any types of verb in V1 resulting two different meaning, respectively: 1) physical action in/into closed space, 2) a condition within the same situation both physical or psychological condition. In (1) physical action in/into a closed space komu was retained its original meaning, but in (2) a conditions within the same situations both physical or psychological condition komu was losing its lexical meaning.